Comparative Study of Compensatory Liver Regeneration in a Rat Model: Portal Vein Ligation Only versus Sequential Ligation of the Portal Vein and Hepatic Artery - Chung, Soo Young; Jeon, Gyeong Sik; Lee, Byungmo (Journal of the Korean Society of Radiology, 2013)
Purpose: To compare the volume change and the regenerative capacity between portal vein ligation (embolization) (PVL) and heterochronous PVL with hepatic artery ligation (HAL) in a rodent model. Materials and Methods: The animals were separated into three groups: group I, ligation of the left lateral and median portal vein branches; group II, completion of PVL, followed by ligation of the same branches of the hepatic artery after 48 h; control group, laparotomy without ligation was performed. Five rats from each group were sacrificed on 1, 3, 5, and 7 days after the operation. Volume change measurement, liver function tests and immunohistochemical analysis were performed. Results: The volume of the nonligated lobe between groups I and II was not significantly different by day 5 and day 7. Mean alanine aminotransferase and total bilirubin levels were significantly higher in group II, while the albumin level was higher in group I. Both c-kit- and MIB-5-positive cells used in the activity detection of regeneration were more prevalent in group I on day 1, 3, and 5, with statistical significance. There was no operation related mortality. Conclusion: PVL alone is safe and effective in compensatory liver regeneration. Performing both PVL and HAL does not confer any additional benefits. KCI Citation Count: 0